Frederick Delius (1862-1934)- His Music as a Tone-Painting Creation among different Cultures - Szulakowska, Jolanta (International Journal of English Literature and Social Sciences (IJELS), 2019)
In this text the work of Frederick Delius is presented in the context of English musical culture at the turn of the XIXth and XXth century. His life is also very interesting because he, as a composer of Dutch origin, became active among different cultures, English and French and more, he took his education in Germany. In my opinion, his music reveals the type of tone-painting due to fact of his method of treating music in the romantic mood and using technical procedures of that time. I managed also to discover and define many topics in his art. These topics that are connected with nature, feelings and the Europen culture help us to understand his music since it can not be examined by commonly known analytical methods. His work one can be outlined as a kind of romantic sensual impressionism. In addition, a picture of the work of Frederick Delius is completed by the descriptions of his best works. This article is based on the large list of documents respecting the life and the work of this composer. An author of the book concerning the French impressionism, Michel Fleury, has included the work of Delius in the circle of the impressionistic composers altogether with Claude Debussy and Maurice Ravel.